Real-World Data on Prognostic Factors for Overall Survival in EGFR-Mutant Non-Small-Cell Lung Cancer Patients with Brain Metastases - Yu, Xiaoqing (J Cancer, 2019)
Background: With the wide application of epidermal growth factor receptor-tyrosine kinase inhibitors (EGFR-TKIs), the survival of EGFR-mutant non-small-cell lung cancer (NSCLC) patients with brain metastasis (BM) has been significantly improved. However, prognosis analysis for patients with EGFR mutation and BM is still lacking, and the prognostic factors remain to be determined. Materials and methods: A total of 746 NSCLC patients with BM were identified between January 2013 and December 2016 at our institution. Overall, 261 patients harboring EGFR mutation and meeting the inclusion criteria for the study were enrolled. Exclusion criteria included KPS<50, diagnosed with BM during treatment with EGFR-TKIs, or insufficient follow-up. Overall survival (OS) was measured from the date of brain metastases. Independent prognostic factors were confirmed using a Cox regression model. Results: The median follow-up time for these patients was 32.7 months (95% CI, 23.5-41.9). The median OS after development of brain metastases was 23.0 months (95% CI, 20.01-25.99). By univariate analysis, significantly shorter OS was noted in patients older than 65 years (p=0.025), KPS <70 (p=0.003), presence of extracranial metastases (ECM) (p=0.00), without intracranial local treatment (p=0.000), and without chemotherapy (p=0.001). There was no difference in OS with respect to EGFR mutation type and number of BM (p=0.343, p=0.729, respectively). The Cox proportional hazards regression model revealed that performance status (KPS<70, p=0.010), ECM (p=0.001), receiving intracranial local treatment (p=0.005) and chemotherapy (p=0.005) were independent prognostic factors for OS, while age was not (p=0.087). Patients with higher diagnosis-specific graded prognostic assessment (DS-GPA) and Lung-molGPA scores corresponded to better prognosis (p=0.000). Conclusion: This retrospective analysis demonstrated that performance status (KPS≥70), absence of ECM metastases, administration of local treatment and chemotherapy were associated with superior OS in patients with EGFR-mutant NSCLC who developed BM. The DS-GPA and Lung-molGPA indexes still applied to NSCLC patients with mutant genotypes and BM.